Protective Immunity after Natural Infection with Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) – Kentucky, USA, 2020. (January 2022) - Spicer, Kevin B.; Glick, Connor; Cavanaugh, Alyson M.; Thoroughman, Douglas
Highlights: This study evaluated protection provided by prior infection with SARS-CoV-2 Overall protection was estimated to be 77% for those aged ≥20 years Individuals aged ≥60 years had decreased protection relative to those aged 20-59 years The level of protection was consistent for up to 9 months after initial infection Work or residence in long-term care was associated with a repeat positive test Abstract: Background: As vaccine supply and access remain limited in many parts of the world, understanding the duration of protection from reinfection after natural infection is important. Methods: Distinct individuals testing positive and negative for SARS-CoV-2 between March 6, 2020, and August 31, 2020, in Kentucky, USA, were identified using the Kentucky National Electronic Disease Surveillance System. Individuals were followed for occurrence of a positive test for SARS-CoV-2 from 91 days after their initial test result through December 31, 2020. Protection from reinfection provided by a prior infection was calculated and additional analyses evaluated impact of age, sex, symptom status, long-term care facility connection, testing occurrence and frequency, and time from initial infection. Results: The protective effect from prior infection was 80.3% (95% CI, 78.2%–82.2%) for those aged 20–59 years and 67.4% (95% CI, 62.8%–71.4%) for those aged ≥60 years. At 30-day time periods through 270 days (with limited exceptions), protection was estimated to be >75% for those aged 20–59 years and >65% for those aged ≥60 years. Factors associated with repeat positive testing included a connection to a long-term care facility, duration of potential exposure, and absence of symptoms during initial infection. Conclusions: Natural infection provides substantial and persistent immunologic protection for a period of several months for most individuals, although subpopulations may be at greater risk of repeat positive testing and potential poor outcomes associated with reinfection. These subgroups include individuals aged ≥60 years, residents and staff of long-term care facilities, and those who have mild or asymptomatic illness with initial infection. Continued emphasis on vaccination and infection prevention and control strategies remains critically important in reducing the risk of reinfection and associated severe outcomes for these groups.